2013
DOI: 10.4028/www.scientific.net/amr.795.711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Milling Time on Particle Size and Surface Morphology of Commercial Zeolite by Planetary Ball Mill

Abstract: Ball milling is a top down approach and a method to reduce size of particle while Zeolite is a valuable inorganic materials having wide variety of applications. In this paper, ball milling of commercial synthetic Zeolite powder was studied with their time varied. Wet ball milling was selected as a potential means to decrease the particle size of Zeolite over dry grinding. The parameters that included in this study were rotational speed, balls to powder ratio, water to powder ratio and milling time. These nanoz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…A strong positive correlation occurred (R 2 > 0.89). The obtained relation is similar to that presented in [52,[84][85][86]. The increase in the size reduction ratio with the increase of S∆ω results from a higher number of contacts between the material and comminution elements occurring for higher angular velocities.…”
Section: Discussionsupporting
confidence: 84%
“…A strong positive correlation occurred (R 2 > 0.89). The obtained relation is similar to that presented in [52,[84][85][86]. The increase in the size reduction ratio with the increase of S∆ω results from a higher number of contacts between the material and comminution elements occurring for higher angular velocities.…”
Section: Discussionsupporting
confidence: 84%
“…The presented results reveal that the prolonged milling time does not affect the powder morphology. This claim seemingly contradicts the observations of other authors [19,20]. Namely, the authors most often used relatively short milling times (for instance 2, 6 or 8 h) and observed a significant reduction in powder particles.…”
Section: Resultsmentioning
confidence: 63%
“…(entry 1). Also, the relatively small amount of catalyst used (5 mol%) that attain the highest yield under ball milling technique, may be due to the effect of ball‐mill that reduce the size of particle of catalyst, accordingly increase the active surface area that exposed to reactants …”
Section: Resultsmentioning
confidence: 99%
“…Depending on the elemental analysis and spectroscopic data of the isolated product, one of the possible products named pyrazolo[3, 4‐d]pyridine derivative 7 was easily ruled out on the basis of the 1 H NMR spectra of the reaction products, due to the presence characteristic singlet signal at δ 7.30 ppm corresponding to the pyrazole proton. To distinguish between the possible occurrence of two isomeric structures 4 or 6, recently, we succeed to utilize the advanced 1 H‐ 15 N HMBC technique to unambiguous the structures of the obtained regioisomers in such cases ,. Taking the product obtained from the reaction of 1 with the aminopyrazole derivative 2 a as representative examples (Scheme ), 1 H‐ 15 N HMBC was obtained for this product where all connectivities were observed for the assignment the nitrogen chemical shifts (Figure ).…”
Section: Resultsmentioning
confidence: 99%